AVAILABILITY OF INFRASTRUCTURE AND CLEAN AND HEALTHY LIVING BEHAVIOR IN PUBLIC AND PRIVATE JUNIOR HIGH SCHOOLS: A COMPARATIVE STUDY - Kartini; Sri Sumarmi (Universitas Airlangga, 2023)
Introduction: Students can achieve a high level of health and obtain good learning achievements by maintaining clean and healthy living behavior (PHBS). Aims: analyze differences in knowledge, attitudes, and practice in private and public junior high school students regarding PHBS. Methods: This research used a comparative design. The study subjects were grade IX students from a private and public junior high school in Surabaya with total sample of 185 students. The observed variables were knowledge, attitude, and practice on clean and healthy living behavior. Data were statistically analyzed using Independent T-test for the continuous data, and chi-square test applied to the categorical data. Result: showed that the average knowledge score of private and public junior high school students is still sufficient (34.5±12.3), while attitude (63.7±10.4) and practice (53.4±6.4) regarding clean and healthy living behavior (PHBS) in private and public junior high school students were categorized as positive and good. Statistical analysis revealed that there was different score for knowledge of PHBS between students in private and public junior high school (p = 0.002), but score of attitude and practice were not different between two groups, with p-value of 0.084 and 0.746, respectively. Conclusion: It concluded that knowledge on clean and healthy living seems not followed by the attitude and practice in daily living of students in state and private junior high school students.